Bridging Reasoning and Results: An Assessment Validation Perspective on the PhD in Design - Luke Feast (She Ji: The Journal of Design, Economics and Innovation, 2023)
This article uses assessment validation as a framework to construct a theory of how to assess a PhD in design. This also has implications for what the PhD degree should be in design. When examiners assess a PhD student’s dissertation or defense, interpretation arguments and use arguments connect the assessment to the ultimate purpose and consequence of the PhD project they assess. My conclusion is that this argument-based approach strengthens the credibility, meaningfulness, and fairness of PhD assessment. The perspective of assessment validation enhances the PhD in design by focusing validation on inferences and assumptions that connect scoring, generalization, extrapolation, and the implications of PhD assessment.